Maternal feeding practices for sick children under 2 years in Wolkite town, Gurage Zone, Central Ethiopia, 2024: a community-based cross-sectional study - Tsehaynew Kasse; Tebibu Solomon Woldesilassie; Abeniezer Gemede Jisso; Arega Abebe Lonsako; Addisalem Haile; Yalemzer Agegnehu Dejene (Journal of Health, Population and Nutrition, 2024)
Abstract Background Optimal feeding practices for sick children are crucial to prevent morbidity and mortality. Despite global and national policies emphasizing the importance of optimal feeding practices for sick children, studies have revealed varying levels of practice in different regions, including Ethiopia. However, there is a research gap in focusing on community-based contexts to determine sick child feeding practices among mothers with young children. Objective To assess maternal feeding practices for sick children under 2 years in Wolkite town, Gurage zone, Central Ethiopia: 2024. Methods A community-based cross-sectional study involving a total of 419 mothers of young children was conducted in Wolkite town, Gurage zone, Central Ethiopia from September 15 to November 15, 2023. Participants were chosen using computer-generated random numbers. Structured, interviewer-administered, and pretested data collection tool were used. The data were coded and entered into EpiData 3.1 before being exported to SPSS version 25 for analysis. Logistic regression was employed to identify factors influencing mothers’ practice. Statistical significance was set at p < 0.05 with a 95% confidence interval. Results The study found that 54.4% (95% CI: 50–59%) of mothers demonstrated good feeding practices for their sick children. Significant factors contributing to these practices included mothers having at least a secondary education (AOR: 3.7, 95% CI: 1.5–9.1), delivering their child in a health facility (AOR: 2.3, 95% CI: 1.4–3.8), and receiving support from the father (AOR: 2.3, 95% CI: 1.4–3.8). Additionally, mothers who were counseled on infant and young child feeding had higher odds of practicing good feeding (AOR: 4.1, 95% CI: 2.3–7.03), access to postnatal care (AOR: 3.8, 95% CI: 2.1–6.95) and having a good knowledge of feeding practices (AOR: 2.5, 95% CI: 1.4–4.5) were also strongly associated with effective feeding practices. Conclusions The study highlights more than half of mothers in Wolkite town, Gurage zone, Central Ethiopia have good sick child feeding practices. Factors such as the higher educational status of the mother, having the father’s support, place of delivery, receiving PNC services, counseling on infant and young child feeding, and knowledge about sick child feeding were significantly associated with their practice. Implementing targeted education programs, strengthening postnatal care services, counseling on infant and young child feeding, and encouraging the involvement of fathers in childcare and feeding were strongly recommended.